Investigating the role of digital capabilities on the relationship between teacher readiness and teacher skills using augmented reality media in elementary schools: A mediation and moderation analysis - Mohammad Archi Maulyda; Sugiman; Wuri Wuryandani; Nawang Sulistyani; Anas Ma'ruf Annizar (Social Sciences and Humanities Open)
This study explores the effect of teachers' digital competencies on their skills in using Augmented Reality (AR) media in elementary schools mediated and moderated by teacher readiness. This explanatory quantitative study used an online survey method to collect data. The participants were 428 elementary school teachers from West Nusa Tenggara, Indonesia. Several experts adopted the instrument and declared it to be highly reliable. Data analysis was conducted using the Confirmatory Factor Analysis (CFA) method to see the factor structure of each variable. After that, linear regression test analysis was conducted to see the relationship between digital competence and teacher skills directly (direct), followed by mediation and moderation analysis to see whether the teacher readiness variable can mediate and moderate the relationship between digital competence and teacher skills using AR media (indirect). The results showed that digital competence significantly impacts teachers' skills in using AR directly, as demonstrated by the results of the linear regression test with a significance value of 0.000 (less than alpha 0.05). Meanwhile, the teacher readiness variable could not be a mediator and moderator because the significance value was more than 0.05. In addition to these findings, researchers also conducted a covariate analysis, which stated that the effect of teacher digital competence on skills in using AR media was influenced by the covariate variables of age and teaching experience with a significance value of 0.003 and 0.000, respectively. In contrast, the gender variable did not have a significant effect. The implications of these findings underscore the importance of developing teachers' digital competencies in adopting AR technology in education while considering factors such as age and teaching experience.